2022
DOI: 10.3389/fcvm.2022.1027000
|View full text |Cite
|
Sign up to set email alerts
|

Association of acetaldehyde dehydrogenase 2 rs671 polymorphism with the occurrence and progression of atrial fibrillation

Abstract: BackgroundAcetaldehyde dehydrogenase 2 (ALDH2) is an essential enzyme in alcohol metabolism, playing a vital function in resisting oxidative stress. Lots of gene variants have been associated with atrial fibrillation (AF), among which the association between ALDH2 rs671 polymorphism and AF is variable. This study aimed to investigate the relationship between ALDH2 rs671 polymorphism and AF occurrence or progression and AF recurrence after catheter ablation.MethodsA total of 924 subjects were enrolled in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have reported that genetic polymorphisms in alcohol metabolism are associated with altered levels of acetaldehyde and differential responses to unpleasant experiences after alcohol consumption [20,21], resulting in increased or decreased susceptibility to habitual alcohol consumption [19,22]. This suggests genetically decreased alcohol metabolism may result in higher acetaldehyde levels, even after drinking small amounts of alcohol, and could cause flushing syndrome increasing the risk of incident AF [22,38]. In our data, individuals in the low PRS tertile group showed the lowest alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that genetic polymorphisms in alcohol metabolism are associated with altered levels of acetaldehyde and differential responses to unpleasant experiences after alcohol consumption [20,21], resulting in increased or decreased susceptibility to habitual alcohol consumption [19,22]. This suggests genetically decreased alcohol metabolism may result in higher acetaldehyde levels, even after drinking small amounts of alcohol, and could cause flushing syndrome increasing the risk of incident AF [22,38]. In our data, individuals in the low PRS tertile group showed the lowest alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%